On the Criterion of Logicality - Pavilionis, Rolandas (Problemos, 1975)
In his article R. Pavilionis analyses the main consequences which follow from adopting the prelogical conception of thinking and proves their inconsistency. The author thinks but that logic is not necessarily connected with verbal thinking – it manifests itself already in the preverbal stage. Inconsistency of thinking does not necessarily mean its prelogicality: modem man operates too with concepts and conceptions which may and sometimes do appear to be inconsistent in the long run of the cognition process.